The effect of psychosocial factors at work on stress and well-being of workers in Mexican restaurants and bars - Saldaña Orozco, Claudia; Gutiérrez-Carvajal, Oscar Iván; Polo-Vargas, Jean David; Ibarra Rentería, Guadalupe Montserrat; Franco, Leidy Alejandra (Cuadernos de Administración, 2024)
There are fewer studies on restaurant, bar, and nightclub workers, and about the work-related psychosocial factors related to work stress and psychological well-being of these workers. This study aimed to examine the relationships between work-related psychosocial factors, work stress, and psychological well-being, through a cross-sectional and correlational research design. The sample consisted of 167 workers (51.9% women and 48.1% men) from restaurants, bars and nightclubs in Jalisco, Mexico. Work-related psychosocial factors were assessed using the revised version by Almirall Hernández et al. (2018) of the psychosocial risk factor scale of the Standard (NOM-035), psychological well-being with the Ryff psychological well-being scale (1989) and work stress with the adaptation to Spanish made by Medina et al. (2007) of the work stress questionnaire of the International Labor Organization ILO. The results showed that leadership, role clarity, work schedule, interference in the work-family relationship, and workplace violence affect work stress. In contrast, workplace violence has an impact on psychological well-being. The need to create strategies to mitigate psychosocial factors that put workers’ mental health at risk is discussed.